HUBUNGAN ANTARA INTERAKSI SOSIAL DENGAN KONSEP DIRI PADA PESERTA DIDIK KELAS VIII MTS - Nurvinta, Yeni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aims to determine the relationship between social interaction with self-concept in class VIII students MTs Negeri 1 Pontianak. The method used is descriptive method with relationship study. The population in this study were as many as 251 students, while the sample in this study were 66 students. Technique of collecting data in this research is indirect communication technique. Data collection tool is a questionnaire. While the technique of data analysis using the formula percentage and product moment. Based on the results of data analysis shows that the social interaction of learners reached 79%, the achievement is in the range of "good". While the self-concept of learners reached 76% are in the range of "good". The result of the analysis of product moment of both variables was obtained 0,603 indicate that there is a significant positive correlation between social interaction with Self concept in class VIII student of MTs Negeri 1 Pontianak.Â Keywords: Social Interaction, SelfÂ  ConceptÂ